The Effect of Erbium, Chromium: YSGG Laser and Fluoride Products on the Resistance of Dental Enamel to Acids - Dhuha Najm Abdulhussein; Aseel Haidar M.J. Al Haidar (Medical Journal of Babylon, 2025)
Even though dental erosion is preventable, it remains widespread and a public health issue. The use of lasers such as erbium chromium is one of the effective preventive tools, particularly when combined with fluoridated products. This review aimed to detect the preventive effect of laser irradiation and fluoridated product applications on inhibiting enamel demineralization. To get accurate information, we conducted a thorough literature search utilizing reliable sources, including journal databases, current systematic reviews, and research recommended by subject matter experts. Studies that met the inclusion requirements had their quality evaluated. The effect of irradiating enamel surfaces coupled with the use of topical fluoride can significantly enhance the resistance of sound enamel surfaces to acids and decrease enamel demineralization more than using laser alone or fluoridated products alone. Combining topical fluoride application with laser irradiation protects sound enamel from demineralization.